Pengaruh Kualitas Produk terhadap Keputusan Pembelian Handphone Merek Oppo di Tanjung Jabung Barat Jambi - Riko Mappadeceng (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The nature of consumers who are more careful in choosing and buying a product shows that the products offered by a company may not necessarily meet the needs and desires of its consumers. Product quality is a potential strategic weapon to beat competitors. So only companies with the best product quality will grow rapidly, and in the long run these companies will be more successful than other companies. The research method used in this research is descriptive and quantitative methods. With a population of students at SMA Negeri 9 Tanjung Jabung Barat Jambi Province and a sample of 83 students.Based on the results of the study, it was obtained that the product quality based on the average overall score was included in the good category. Students choose Oppo cellphones becauseproduct technology compared to other products is very good, but for the design and product variants compared to other products it is not very good. Then regarding purchasing decisions, according to respondents, the ease of obtaining information about the products purchased is very good. While individual interest in following technological developments is included in the good category. The results obtained indicate that there is a significant positive effect between product quality on the purchase decision of Oppo Mobile at SMA Negeri 9 Tanjung Jabung Barat.